pengaruh stres pengaruh stres kerja terhadap kinerja karyawan di universitas muhammadiyah palopo : pengaruh stres kerja terhadap kinerja karyawan universitas muhammadiyah palopo - nurlela; haedar; lita sriyanti (RESEARCH FAIR UNISRI, 2024)
This research aims to determine the effect of work stress on employee performance at Muhammadiyah University of Palopo. This research was conducted using quantitative methods. The population and sample used were all employees, totaling 34 employees. The sample in the study used a saturated sampling technique, namely all employees of the Muhammadiyah University of Palopo. The data used in this research is primary data in the form of a questionnaire. From this research it was found that there is an influence between the work stress variable (X) on employee performance (Y). This is proven through hypothesis testing using the t test. Where the results obtained with t count are greater than t table, namely t count (3.493) > t table (1.694). So H1 is accepted or "Job stress has a significant effect on employee performance at Muhammadiyah University of Palopo". The magnitude of the influence that work stress has on employee performance is obtained by an Adjusted R Square (coefficient of determination) value of 0.253, which means the influence of the independent variable (X) on (Y) is 25.3%. The reliability test in this research used Cronbach Alpha with the help of the SPSS (Statistical Package For Social Sciences) version 24 program. Cronbach Alpha is a benchmark used to describe the correlation or relationship between scales created with all existing variable scales. The instrument used in this variable is said to be reliable and has a Cronbach Alpha of more than 0.6. It is hoped that the results of this research can provide information as a basis for consideration, support and contribution of thought regarding the influence of work stress on employee performance. The limitations of the research are: Lack of samples studied, in this research, using job stress (X) and employee performance (Y) variables.